Conveying transparency. Case study of Spanish university archive departments - R. Pacios, Ana; Torreiro Rodríguez, Iria; Moro Cavero, María Manuela (Revista General de Información y Documentación, 2019)
The Spanish Transparency Act in effect since 2014 requires public institutions to upload to their websites and periodically update any information of consequence to guarantee a transparent government landscape. University archive departments, which are indispensable for the transparency of the institutions they serve, should also publish their own information, an initiative that would indisputably enhance their visibility, credibility and image. This study assessed archive department transparency on the grounds of the presence of a series of indicators on their websites. Although examples of good practice were identified, information was found to be scant in certain essential areas, in particular lines of action, organizational objectives and yearly reports.